(untitled) (Journal of Kidney Cancer, 2024)
Enhancing renal masses are conventionally treated as malignant unless proven otherwise due to the difficulty distinguishing between malignant and benign tumors based on imaging. Data from the Western registries suggests overtreatment of renal tumors with a Benign Kidney Tumor Resection Rate (BKTRR) ranging from 10 to 33%, with an increasing trend. Since robust, population-based data from India was unavailable, we sought to determine BKTRR in an apex cancer institute, which would provide insight into the rates in the community. The institutional kidney tumor database was queried for all patients aged ≥18 years with renal neoplasms between January 2000 and December 2022. Patients who underwent surgery, either radical or partial nephrectomy, with intent to cure were analyzed and the BKTRR during the study period was evaluated. A total of 330 patients underwent surgery for renal tumors presumed to be malignant. A final pathologic diagnosis of the benign tumor was made in 16 (4.8%) patients, comprising 7.2, 7.2, and 3.7% of resections with LTD ≤4, 4–7, and >7 cm, respectively. Asymptomatic benign tumors ≤7 cm comprised 3.0% of all resections, and these were potentially unnecessary surgeries. A multivariable analysis suggested that no patient or imaging characteristic could predict a final benign extirpative pathology. Our study suggests a lower rate of BKTRR compared to the published international literature but is likely to be the lower limit of that in the community. Population-based studies are required to determine the true BKTRR and the quantum of potentially unnecessary surgeries for benign kidney tumors.